Sexual harassment - 20160731 frey50; Gillard, Arthur (Farmington Hills, Mich. Greenhaven Press, 2014)
Discusses an issue by presenting multiple sides to current issues by focusing on concerns that today's middle and high school students deal with regularly. Moreover, Issues That Concern You recognizes the intimate relationship between its subject and reader as it weaves together different points of view. Backmatter offers facts and "self-help" style advice to young people grappling with the issues.
An overview of sexual harassment -- Why men can't - and shouldn't - stop staring at women -- Sexual harassment is about power, not desire -- Sexual harassment in school is a serious problem -- PC police target middle and high school students -- Online sexual harassment is a serious problem -- Mobile online technology is helping combat sexual harassment -- Public sexual harassment ("street harassment') is a serious problem that requires legal regulation -- Women need to confront sexual harassers -- Men need to take an active role in ending sexual harassment -- Abuse of power: an increase in male-on-male sexual harassment shows larger truths about abuse in the workplace -- Women dressing provocatively does not contribute to sexual harassment -- A woman describes the negative effects of sexual harassment she experienced in her youth -- Appendix -- Organizations to contact -- Bibliography -- Index.
Keywords: Sexual harassment of women -- United States; Sexual harassment of men -- United States; Sexual harassment of men; Sexual harassment of women; United States; Juvenile works